PENGARUH PENGUNGKAPAN ENVIRONMENT, SOCIAL, GOVERNANCE (ESG) TERHADAP PROFITABILITAS PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar dalam Index KOMPAS 100 periode 2019-2021) - Valiant Darma Pangentas; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2023)
This research aims to analyze the effect of ESG disclosure on company profitability with Environment, Social, Governance Disclosure as independent variables which allegedly influence the dependent variable, Return On Assets. The population in this study consists of companies listed in the KOMPAS100 index in the 2019-2021 period. Samples were taken using purposive sampling method and resulted in 47 companies with 3 analysis periods so that the total sample was 141. Hypothesis testing was carried out using multiple linear regression method and processed using IBM SPSS 26.0 software. The results of this study explain that Environment Disclosure has a positive effect on Return On Asset, Social Disclosure has a negative effect on Return On Asset and Governance Disclosure has a negative effect on Return On Asset.